Multicultural Education Praxis for Primary Schools: Perspective of Muhammadiyah Primary Schools Indonesia - Ferdian Noor, Ady; Rifaldi KhunaifiSupardi, A’am; Sukirno; Haryanto (International Journal of Psychosocial Rehabilitation, 2019)
Cultural and ethnic diversity as a national force. Muhammadiyah rationalizing against tradition in the community resulted in the loss of cultural unity prone unity. Muhammadiyah school system has a role in growing individualism symptoms, such as impersonal and transactional relationship with the student’s teacher, school alumni, and students who thrive in a capitalist society. The purpose of this study to support the multicultural education indicators can be constructed and combined with religious-based education Muhammadiyah. The research method used is a Quantitative Approach with a descriptive analytical type. Descriptive analytic is research by outlining and analyzing. The total research subjects were 92 people. The questionnaire was made based on indicators of the construct of multicultural education so that a multicultural education perspective for Muhammadiyah elementary schools will be obtained. The result are Muhammadiyah Primary Schools Palangkaraya was able to develop multicultural education indicators. The implictions this study are expected to make the government’s foundation for designing and making policies that can be accommodated by all parties. Multicultural education policies that adopt the concept of early adaptation (hybridization) indicators of multicultural education integrated with religion